Customer Experience, Religiosity, and Social Status Determining Tourist Visits in East Java Halal Tourism - Nabilah Ahsanah Saffanah; Moh Farih Fahmi (International Conference on Islamic Economic (ICIE), 2026)
The tourism sector plays a strategic role in economic growth, yet shifting tourist motivations toward comfort, halal lifestyle, and social recognition create new challenges for destination managers. This study aims to examine how customer experience, religiosity, and social status influence tourists’ visiting decisions at the Al-Akbar National Mosque in Surabaya. A quantitative associative approach was employed using purposive sampling, generating 115 respondents. Data were analyzed through multiple linear regression to test the proposed hypotheses within the Stimulus-Organism-Response framework. The findings reveal that customer experience has a positive and significant effect, highlighting the importance of service quality and environmental comfort. Religiosity also significantly influences decisions, confirming spirituality as a primary driver. Meanwhile, social status exerts a partial but meaningful effect, indicating that visits are also shaped by lifestyle and self-actualization needs. This study contributes theoretically by enriching halal tourism literature through an integrated behavioral model, and practically by offering insights for tourism managers to design experience-based marketing strategies that align service excellence with religious and social values in contemporary tourism contexts.